1988
DOI: 10.1016/0014-5793(88)80799-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the site on bovine hormone‐sensitive lipase phosphorylated by cyclic AMP‐dependent protein kinase

Abstract: The primary structure of a region on hormone‐sensitive lipase was determined to be: Lys‐Thr‐Glu‐Pro‐Met‐Arg‐Arg‐Ser‐Val‐Ser‐Glu‐Ala‐Ala‐Leu‐Thr‐Gln‐Pro‐Glu‐Gly‐Pro‐Leu‐Gly‐Thr‐Asp‐Ser‐Leu‐Lys. Ser‐8 was the only residue in the intact protein phosphorylated by cyclic AMP‐dependent protein kinase. However, Ser‐10 also appeared to be present in a phosphorylated form, suggesting that it is a target for a distinct protein kinase in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
73
0
3

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 19 publications
5
73
0
3
Order By: Relevance
“…A key feature of HSL is its ability to be activated by phosphorylation by cyclic AMPdependent protein kinase [5][6][7]. Consistent ~ith this, Goldberg cell-free extracts of P388D~ macrophages by cyclic AMP-dependent protein kinase, and in intact cells by elevation of intracellular cyclic AMP levels [81.…”
Section: Introductionmentioning
confidence: 99%
“…A key feature of HSL is its ability to be activated by phosphorylation by cyclic AMPdependent protein kinase [5][6][7]. Consistent ~ith this, Goldberg cell-free extracts of P388D~ macrophages by cyclic AMP-dependent protein kinase, and in intact cells by elevation of intracellular cyclic AMP levels [81.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that tryptic phosphopeptides containing the site on bovine HSL which is phosphorylated by cyclic-AMP-dependent protein kinase (SVSEAALTQPEG-PLGTDSLK) also contain a second phosphorylated residue (SVSEAALTQPEGPLGTDSLK) (site 2), which is not modified by cyclic-AMP-dependent protein kinase, but which is already partially phosphorylated in the enzyme, as prepared, indicating that this residue represents an in vivo site of phosphorylation [5]. Work with rat adipocytes has also demonstrated the presence of a second site of phosphorylation on Carrespondence to…”
mentioning
confidence: 99%
“…This leads to phosphorylation of HSL which activates the enzyme and therefore stimulates lipolysis [2]. The major antilipolytic hormone is insulin which acts, at least in part, by reducing the intracellular cyclic AMP concentration [3].HSL is phosphorylated at a single site by cyclic-AMPdependent protein kinase in vitro [4,5]. Peptide-mapping studies indicate that this site, which has been termed the regulatory site, is that which is phosphorylated in intact adipocytes in response to noradrenaline [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HSL is also present in the steroidogenic tissues [3-61, where it functions as a cholesterol ester hydrolase and has been proposed to play an important regulatory role in the synthesis [3] and also hydrolysis [7] of steroid hormones from these tissues. The activity of HSL is under strict hormonal and neural control, a mechanism involving phosphorylation of a single serine residue (Ser-563) [6,8] by cylic AMP-dependent protein kinase [9,10]. In response to lipolytic hormones, such as noradrenaline, HSL is phosphorylated and concomitantly activated, whereas antilipolytic hormones, such as insulin, cause a net dephosphorylation and deactivation.…”
Section: Introductionmentioning
confidence: 99%